El discurso docente y la pregunta como estrategia didáctica para generar reflexión crítica de contenidos. - Jaime Rosales Ma., Carmen Eugenia (Universidad Técnica de Machala, 2019)
The work presented is the result of two years of research in a context of the Advanced Technical Degree learning centers in ICT’s fields, in the northeast region of the state of Guanajuato, Mexico. This investigation ran through three stages: Recovery, Problematization and Innovation of the teaching practices with the following objective: Through the application of innovative ideas, create a route within the teaching methods to manage and promote an open dialogue and criticism between students, not only academically but socially and personally. Understanding investigation-action as a study of the social context with the purpose of improving the action in itself, it works out as a self-inquiring reflexion, which is a cyclic process in research. Starting from the innovation-intervention structure, an improvement of the criticalroute was promoted between the students (Martínez-Otero 2010 & Fisher 2013) from the 1st and 2nd levels to the 3rd one in general terms it meant a progress of 80% of the focus group. The results are encouraging although these would involve new investigations and reflections around different strategies to foster a critical comprehension. Furthermore, it is necessary to do research and act upon the cognition processes of the students.
El trabajo que se muestra es el resultado de dos años de investigación en el contexto de las aulas del nivel Técnico Superior Universitario en el área de las TIC ́s, en la región nordeste del estado de Guanajuato México. Ésta abarcó tres momentos: Recuperación, Problematización e Innovación de la práctica docente, buscando mediante la aplicación de los ejes de innovación, generar en la práctica docente un camino que gestione y promueva en los estudiantes el diálogo y la criticidad, no únicamente en el ámbito escolar, sino también en el social y personal. Es a través de la investigación-acción, entendiéndola como el estudio de la situación social a fin de mejorar la acción sobre la misma, una forma de auto indagación reflexiva. A partir de la estructura de innovación-intervención se promovió en los estudiantes el avance dentro de una ruta crítica (Martínez-Otero 2010 y Fisher 2013) de los nivel 1 y 2 al nivel 3 que en términos generales significó un progreso del 80% del grupo estudiado. Los resultados son alentadores aunque éstos supondrían nuevas indagaciones y reflexiones en torno a otras estrategias que propicien la comprensión crítica; asimismo es necesario investigar sobre los propios procesos cognitivos de los estudiantes.
Keywords: PROBLEMATIZACIÓN; RUTA CRÍTICA; INVESTIGACIÓN-ACCIÓN; DIÁLOGO Y CRITICIDAD